Quantifying differences in the material properties of the fiber regions of the pectoralis major using ultrasound shear wave elastography. (3rd October 2017) - Leonardis, Joshua M.; Desmet, David M.; Lipps, David B.
Abstract: The sternocostal and clavicular regions of the pectoralis major are independently harvested to provide shoulder stability, but surgical decision making does not consider the biomechanical consequences that disinsertion of one fiber region over the other has on shoulder function. Differences in material properties between the fiber regions could influence which tissue is more optimal for surgical harvesting. The current study utilized ultrasound shear wave elastography (SWE) to investigate whether the in vivo material properties differ between the fiber regions. Shear wave velocities (SWVs) were collected from the sternocostal and clavicular fiber regions of the pectoralis major from ten healthy young male participants. Participants produced isometric shoulder torques of varying magnitudes (passive, 15%, and 30% MVC) and directions (horizontal and vertical adduction). Four shoulder positions encompassing different vertical abduction and external rotation angles were examined. One-way ANOVAs tested the hypotheses that differences in SWVs during rest existed between the fiber regions as a function of shoulder position, and differences in SWVs during contraction existed as a function of shoulder position and torque direction. In all shoulder positions, the clavicular region exhibited greater SWVs during rest than the sternocostal region ( P  < 0.001). In shoulder positions that did not include external rotation, the clavicular region exhibited greater SWVs during contraction when producing horizontal adduction torques ( P  < 0.001), while the sternocostal region exhibited greater SWVs during contraction when producing vertical adduction torques at 30% MVC ( P  < 0.01). Our results suggest that each fiber region of the pectoralis major provides unique contributions to passive and active shoulder function.